Surface modification of poly (L-lactic acid) to improve endothelial cell-material interaction - Xia, Yun (2011)
Poly (L-lactic acid) (PLLA) is recognized as one of promising materials for cardiovascular applications, attributed to its mechanical and degradative properties which could match with human artery healing process. However, endothelialization on PLLA appears difficult due to its hydrophobicity and poor cell affinity. In this work, a mild and easily-controlled surface modification method was developed to immobilize biomolecules (gelatin and chitosan) on PLLA, which is considered as a significant contribution. This three-step surface modification method involved argon (Ar) plasma treatment, acrylic acid grafting polymerization and covalent coupling reaction between amine groups and carboxylic groups. Surface characterization techniques, including X-ray photoelectron spectroscopy (XPS), contact angle measurement and colorimetric methods for surface density of functional groups, proved the feasibility and stability of this surface modification method. Immobilization of these biomolecules is found to increase the surface wettability and to alter the surface chemistry of PLLA. EC-biomaterial interaction study demonstrated that gelatin and chitosan modified PLLA had better cell affinity and promoted endothelialization. Human umbilical vein endothelial cells (HUVEC) cultured on modified PLLA exhibited improved cell adhesion, proliferation and retention under shear stress. Further study on cell adhesion strengthening mechanism on various PLLA substrates revealed the positive correlation between the cell adhesion strength with cell spreading, focal adhesion size and number-per-cell, as well as fibronectin fibril formation. Surface physiochemical properties were found to modulate the cell adhesion strength through regulating cell-biomaterial interactions. There has been no previous report of a quantitative correlation of these parameters to adhesion strength.